TECHNOLOGY-BASED LEARNING INNOVATION TO IMPROVE THE QUALITY OF EDUCATION IN THE DIGITAL ERA - Annisa Mayasari; Devi Sulaeman; Opan Arifudin; Belina Anggia Gustami; Rizqy Nur Sholihat (International Journal of Social Science, Educational, Economics, Agriculture Research and Technology (IJSET), 2026)
The use of technology in the learning process can increase student learning motivation, accelerate conceptual understanding, and encourage the creation of a more interactive and engaging learning environment. This study aims to understand and describe technology-based learning innovations implemented in Islamic senior high schools (madrasah aliyah) to improve the quality of education in the digital era. The methodology used was a qualitative case study approach, conducted in one of the Islamic senior high schools in an urban area. Data were collected through in-depth interviews, participant observation, and documentation during the implementation of technological innovations in learning. The results show that the application of technology, such as the use of online learning platforms, digital media, and interactive tools, can increase student learning motivation and the effectiveness of the learning process. However, the success of these innovations is also influenced by factors such as teacher readiness in integrating technology, available facilities, and support from madrasah management. These findings conclude that technology-based learning innovations have great potential to improve the quality of education in Islamic senior high schools, provided they are supported by adequate training and the development of relevant digital learning resources. This study contributes to the development of innovative models of technology-based learning that are adaptive and sustainable in the digital era.